WORKLOAD ANALYSIS OF BANQUET DAILY WORKER ON SMARTFREN ANNUAL DISTRIBUTOR CONFERENCE 2018 - Ni Wayan Sunarti; Ni Ketut Bagiastuti; Ni Nyoman Triyuni (Politeknik Negeri Bali, 2018)
The Westin Resort Nusa Dua Bali is one of the hotels that often hold conferences. Usually the arrangements of conference handled by Banquet Department. One of conference that has been held is Smartfren Annual Distributor Conference 2018. The holding of this conference makes the workload of Banquet Department increases, while the employee owned only 17 people. So hiring daily worker becomes the best choice. To determine total of banquet daily worker , the data analysis technique used is the workload analysis. Using this data analysis technique got result of calculation of work load analysis based on hotel provisions required daily worker 24 people. However, the results of the analysis calculations obtained based on the reality experienced is different, daily worker banquet is 30 people. Looking at the two calculations there is a difference, this because due to lack of knowledge of the daily worker, the absence of calculations for daily worker needs and the demand for daily worker is always abrupt. The existence of this study, is expected in determining total of daily worker needs to be more effective.